Սովի վկայությունները ԺԷ. դարասկզբի հայ մատենագրության մեջ - Հարությունյան, Արսեն (Մատենադարան)
The ordeals that befell the Armenian people in the early 17th century were first and foremost a direct result of the long Turkish-Iranian wars, and the main purpose of the clashes between the two countries, Ottoman Turkey and Safavid Iran, was gaining access to the resources of Armenia, trade routes and land rights. This was the reason why Shah Abbas's strategy was based on the deportation of Armenians and the destruction of all possible means for the activity of the enemy (in this case, the Turks). This was especially manifested in burning fields and orchards, the destruction of natural resources, dehidration of the soil, imposition of high taxes and duties etc. This resulted in the shortage of bread and the rise in prices (especially in the land of Ararat), which were repeatedly evidenced by the literary sources and in fact led to severe famine. Выпавшие на долю армянского народа в начале XVII века испытания явились прямым следствием затяжных ирано-турецких войн, основной целью которых было завоевание земель и ресурсов Армении, проходящих через нее торговых путей. Шах-Аббас стремился любой ценой изгнать армян со своих земель и уничтожить все ресурсы, которые могли бы понадобиться врагу (туркам). По его приказу поджигались посевы и сады, уничтожались припасы, иссушались земли, были установлены высокие налоги и подати. Именно следствием этого стали многократно засвидетельствованные в исторических источниках дороговизна и недостаток хлеба, в особенности в Араратской области, что фактически привело к массовому голоду.
Keywords: Հիշատակություններ; Միջազգային առցանց գիտաժողով